Reinterpretasi Hadis Perempuan Di Ruang Publik Perspektif Feminisme Sosialis - Nur Ikhlas; Ahmad Hifni (Jurnal Ulunnuha, 2022)
Hadith for women is prohibited without a mahram, including one of the topics of hadith that is quite well known, not only for hadith experts, but also warm among jurists. certain, believe that women are prohibited from going without a mahram, other parts of the hadith are temporal so that they are not relevant to use in the current situation and situation. Because the hadith describes the conditions at the time of the Prophet and his companions, not the current conditions. This paper compares the hadith that is forbidden without a mahram with the hadith that can be used by women without a mahram. Then it will try to give a new meaning (reinterpretation) based on the compromise results of the hadiths that seem "opposite" and are studied with a feminist approach with the aim of giving birth to a new understanding so that religious texts, especially regarding nature without a mahram, do not seem to shackle women. The type of method used in this research is qualitative with the approach of Socialist Feminism, where gender occurs because of the ancient capitalist system and the domination over women. This paper concludes that the hadith about for a woman without a mahram is tentative and is the impact of the class structure in the Arab world first. This had an impact on gender and sexually subordinated women at that time